Bacteriological aspects of bovine carcass - Telles, Francisco José S.; Martins, Carlos B.; Maia, Geraldo A.; Monteiro, José Carlos S. (Pesquisa Agropecuaria Brasileira, 2014)
Total count of mesophilic and psycrophilic bacteriae on the surface of bovine carcasses was made after dressing, in 48 and 180 - hour storage intervals at 0 °C. Values equal to or higher than 1 x 106 bacterian cells were found right after dressing, and in the control; such values are considered high, according to the microbiological patterns generally admitted. Studies were made on the frequency of Salmonella, Staphylococcus and Californus, and a high number of the two latter groups was found. Bacteria belonging to the Salmonella genus were not isolated. Chlorine applications in concentrations of 50 ppm, 100 ppm and 200 ppm were used, and the last one was the most efficient showing a reduction of 51.7% and 55.7%, respectively, for mesophilic and psychrophilic bacteriae on the carcass surface, in relation to the control. The bacteria genera most frequently found were: Enterobacter, Escherichia, Proteus, Citrobacter, Streptococcus and Staphylococcus.